Dentistry and the COVID-19 Outbreak - Luís Filipe Lima Sobral Amante; João Torres Monteiro Afonso; Greta Skrupskelyte (Elsevier, 2021)
Introduction: Infection prevention in dental practice is a principle of utmost importance aiming to protect patients, the dental team, and ultimately, public health. The recent pandemic of coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has instigated worldwide public concern. This highly contagious disease has called for profound changes in patient care around the world. The goal of this article is to review the current literature and introduce essential knowledge about COVID-19, recommend management protocols and adequate protection for dental professionals during the outbreak. Material and methods: The literature search was conducted from April to June 2020. After full-text screening a total of 85 studies were included. Results: Given the novelty of SARS-CoV-2, some characteristics of the virus remain yet unknown. The virus is aerosol-transmissible and, because of the nature of dental procedures, this puts dental professionals and patients at a high risk of contamination by this pathogen. Adequate management protocols and specific protective approaches are essential to minimise the spread of COVID-19 in dental settings during the outbreak. Discussion: The overall impact of COVID-19 in health care worldwide is yet to be determined. This constitutes a significant limitation to this review because the information obtained risks being outdated as the pandemic progresses. The prudent practitioner will use this review as a starting point and continue to proactively update themselves as the outbreak continues. Further studies are required to investigate the potential impact of infections with SARS-CoV-2 within dental settings.